Computable General-Equilibrium Modeling of Afghanistan Growth Opportunities - Estrades, Carmen; Campoy, Diego (World Bank, Washington, DC, 2018)
This paper presents a general equilibrium analysis applied to evaluate different growth policy options for Afghanistan. The analysis is part of a larger analytical work program undertaken by the World Bank which aims at enhancing understanding of Afghanistan’s growth and fragility challenges. In this paper, the authors analyze the potential growth drivers from the increase in foreign aid as well as from the implementation of a series of reforms and pubic investment options, specifically in mining and agriculture. The paper is structured as follows: The authors first present the structure of the Computable General Equilibrium (CGE) model and the data used to calibrate it. Then, the authors present the baseline scenario and the simulation scenarios. Finally, the authors present results from the simulation scenario and draw some conclusions.